2021
DOI: 10.1007/s43154-021-00053-6
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of Corporeal, Co-present Robots as Agents of Influence: a Review

Abstract: Purpose of Review To summarize the set of roboethics issues that uniquely arise due to the corporeality and physical interaction modalities afforded by robots, irrespective of the degree of artificial intelligence present in the system. Recent Findings One of the recent trends in the discussion of ethics of emerging technologies has been the treatment of roboethics issues as those of “embodied AI,” a subset of AI ethics. In contrast to AI, however, robots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This point of view is supported by governmental organizations, for example the European Parliament resolution on a comprehensive European industrial policy on AI and robotics notes that "automated weapons systems should continue to have a human-in-command approach to artificial intelligence" [46]. A survey from 2015 has indicated that the majority of people opposes use of LAWS for offensive purposes and supports international ban of LAWS [47]. If International Humanitarian Law does allow the use of LAWS, it would be the up to robot engineers to create algorithms that determine the extent of human involvement for ethical robotic warfare [48].…”
Section: Functionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…This point of view is supported by governmental organizations, for example the European Parliament resolution on a comprehensive European industrial policy on AI and robotics notes that "automated weapons systems should continue to have a human-in-command approach to artificial intelligence" [46]. A survey from 2015 has indicated that the majority of people opposes use of LAWS for offensive purposes and supports international ban of LAWS [47]. If International Humanitarian Law does allow the use of LAWS, it would be the up to robot engineers to create algorithms that determine the extent of human involvement for ethical robotic warfare [48].…”
Section: Functionalitymentioning
confidence: 99%
“…The study of the ethics of robotics, or roboethics, was pioneered by by Gianmarco Veruggio in the early 2000s [5]. Since then, roboethics and AI ethics have become widely discussed topics, with the number of publications mentioning either of the terms increasing tenfold in the last 5 years [6]. Although many organizations already propose well-considered ethical principles for robotics and AI, the need remains for enforceable ethical regulations on governmental and international levels.…”
Section: Introductionmentioning
confidence: 99%
“…Robot recommendations that lead to product purchase is an interesting event for sellers; however, some researchers argue that the benefits to consumers should also be fully taken into consideration [32] [33]. They are worried that robotic recommendations could lead to unnecessary purchases for consumers sometimes.…”
Section: G Potential Ethical Issuesmentioning
confidence: 99%
“…Further, we have decided to include both AI and robotics policies in this overview. There are significant similarities in the ethics of robotics and AI, especially if we view robots as embodied AI [6]. The governments have also dedicated more attention to regulation of AI, most likely because AI technology is being actively incorporated in all aspects of life.…”
Section: Roboethics and Ai Policies In North America And Europementioning
confidence: 99%
“…The study of the ethics of robotics, or roboethics, was pioneered by by Gianmarco Veruggio in the early 2000s [5]. Since then, roboethics and AI ethics have become widely discussed topics, with the number of publications mentioning either of the terms increasing tenfold in the last 5 years [6]. Although many organizations already propose well-considered ethical principles for robotics and AI, the need remains for enforceable ethical regulations on governmental and international levels.…”
Section: Introductionmentioning
confidence: 99%